Field notes contributed by Jim Sinclair, fall 1996 - Sinclair, Jimet al (1996)
List of birds and locations contributed by Jim Sinclair. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1996. Epson - sheet feed